BOARD ETHNICITY AND SUSTAINABILITY REPORTING - Osayantin Aifuwa, Hope; Kamaldeen Usman, Muhammed; Lawal Subair, Muhammed; Temidayo Philip, Gideon; Hussien, Kerimu (Copernican Journal of Finance & Accounting, 2022)
The aim of this study is to investigate the relationship between board ethnicity and sustainability reporting of listed deposit money banks in Nigeria from the period 2013–2020. The study examined the impact board members’ interaction from major and minor ethnic groups have on the sustainability reporting of listed deposit money banks. Secondary data was collected from annual reports and account of listed deposit money banks from the Nigeria Stock Exchange website. Results from the panel least squares regression revealed that the proportion of directors from HAUSA ethnic group have a positive influence on sustainability reporting; while the proportion of directors from YORUBA ethnic group negatively affects sustainability reporting. Furthermore, on the example of major and minor ethnic groups, it was found that the presence of directors from HAUSA and YORUBA ethnic groups; and HAUSA, YORUBA, IGBO and MINOR ethnic groups have negative and significant impact on sustainability reporting of listed deposit money banks in Nigeria. The study concluded that banks should employ the services of directors from both major and minor ethnic groups to improve the extent of sustainability reporting. Also, financial institutions, specifically deposit money banks should increase the representation of directors from IGBO and MINOR ethnic groups.